(untitled) (Fiep Bulletin - online, 2013)
This research aimed to evaluate the effectiveness of a social project of exercise in changing the lifestyle and quality of life of older adults; compare the physical activity level of project participants Live Life with Health in relation to non-participating , to identify the relationship between lifestyle and quality of life. This research has a quantitative approach, the type Survey, cross held by a questionnaire. The sample consisted of adults aged 40 or more, as follows: 33 participants in Project Viva life with health (AF-PRO), and 44 nonparticipants (queue the Health Post - FE). It was found that as the health hazards, there is smoking in 20.45% of the FE group and 3.13% in group AF-PRO, hypertension 63.64% for EF and AF-PRO with 54.55% ; higher prevalence of joint pain in the FE group (84.09% and 60.45% in the lumbar knees). There is significant difference in physical activity during leisure time (48.48% of the AF PRO-reported practice, compared to 22.73% of FE and FE of the 44 evaluated, only 22.73% reported performing some type of physical activity regular. conclude that the practice of physical activity planned and supervised by trained professionals, ie, physical Educators, participants have access to knowledge that promote greater awareness of the importance of an active lifestyle, as well as lifestyle healthy.